Al Titudinal Variation in Chlorophyll Fluorescence/Photosynthetic Efficiency in Seedlings of some Indigenous Fodder Species - Husen, Azamal; Krall, Rakesh; Nautlyal, S. (Indian Forester, 2004)
Chlorophyll fluorescence variation studies of five indigenous fodder tree species were conducted at three altitude (640, 1200 and 1800m) in Garhwal Himalayas to find out the photosynthetically most active, photosynthetic efficiency of these species as influenced by altitude as well as to understand the adaptation potential of a species along with altitudinal gradient. Pronounced variation in photochemical efficiency of photosystem II was recorded as Fv/Fm ratio on fully developed leaves in sunny days. Among the tested species Grewia optiva, Bauhinia purpurea, Melia azedarach and Celtis australis showed reduction in Fv/Fm ratio with increasing altitude. However, in Quercus leucotrichophora Fv/Fm ratio increased with increasing altitude. The extent of chlorophyll fluorescence variation at three altitudes was probably due to the habitat specific liking of individual species orl environmental variation has been discussed in the present communication.